Use of the concept ‘environmentally relevant level’ in linking the results of pesticide toxicity studies to public health outcomes - Robin Mesnage; Charles Benbrook (All Life, 2023)
Evidence is growing that human exposures to pesticides are contributing in a myriad of complex ways to chronic disease. Regulatory and public health agencies have struggled for years with the definition of acceptable exposure thresholds. At the same time, scientists are trying to design studies so that a chemical is delivered at ‘environmentally relevant levels.’ The aim of this review is to: (1) explain the many factors that must be taken into account in determining environmentally relevant levels or doses; (2) improve the ability to properly translate results from laboratory studies into human-health risk assessment; (3) enhance opportunities to compare results across studies using different experimental designs, organisms and routes of exposure. We found that confusion over the relationship between concentrations, dosing levels, regulatory thresholds and ‘safe’ exposure levels is common. We provide recommendations to scientists and authors, peer reviewers and journal editors in the hope of advancing understanding of how to design, carry out, interpret and explain the real-world significance of both old and new lines of scientific inquiry.